1959
DOI: 10.1139/z59-019
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Affecting Diapause in the European Corn Borer, Ostrinia Nubilalis (Hbn.) (Lepidoptera: Pyralidae)

Abstract: At 65" F, the percentage of larvae of the European corn borer entering diapause increased from practically 0 to 95 as the photoperiod was increased from 0 to 9.5-14 hours of light per day, and decreased sharply to a minimum of 3 as photoperiod was increased to 16 or more hours of light per day. Rearing and studies on oxygen consumption revealed that, to be most effective, exposure to factors inducing diapause must begin before the second day of the final instar, and must continue for a period equivalent to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1960
1960
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 2 publications
1
16
0
1
Order By: Relevance
“…Many such thresholds have been proposed in the literature (see Beck, 1980Beck, , 1983b for reviews), including some that are independent of photoperiod. Mutchmor & Beckel (1959) proposed a photoperiod threshold of 14.5-15.0 h light/day. Beck & Hanec (1960) reported a photoperiod threshold of 15.0 h for larvae reared at 26 ~ C and 15.5 h for larvae reared at 21 ~ Investigators reported later that the duration of the dark cycle, or scotophase, was actually controlling expression of diapause in ECB (Beck, 1980;Bowen & Skopik, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Many such thresholds have been proposed in the literature (see Beck, 1980Beck, , 1983b for reviews), including some that are independent of photoperiod. Mutchmor & Beckel (1959) proposed a photoperiod threshold of 14.5-15.0 h light/day. Beck & Hanec (1960) reported a photoperiod threshold of 15.0 h for larvae reared at 26 ~ C and 15.5 h for larvae reared at 21 ~ Investigators reported later that the duration of the dark cycle, or scotophase, was actually controlling expression of diapause in ECB (Beck, 1980;Bowen & Skopik, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Facultative diapause is induced at the larval stage by a short daylength and lowering temperature (Mutchmor & Beckel, 1959;Beck & Hanec, 1960). Facultative diapause is induced at the larval stage by a short daylength and lowering temperature (Mutchmor & Beckel, 1959;Beck & Hanec, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…The adzuki bean borer, Ostrinia scapulalis (Walker) (Lepidoptera: Crambidae), is a multivoltine insect (one generation in spring and one or two generations in summer). Facultative diapause is induced at the larval stage by a short daylength and lowering temperature (Mutchmor & Beckel, 1959;Beck & Hanec, 1960). In nature, the fifth (last) instar of O. scapulalis cease feeding and enter diapause in late summer (August-September).…”
Section: Introductionmentioning
confidence: 99%
“…Photoperiod, temperature and heredity (races) are the main factors affecting the induction and termination of overwintering diapause for EBC (Onstad & Brewer, ). Its diapause is prevented by high temperatures (>24 °C) and day‐lengths higher than 14.5 hours (Mutchmor & Beckel, ). However, under a photoperiod of 12 h of light per day, temperature higher than 17.5 °C during the scotophase (night) will prevent diapause induction, due to an interaction between those two factors (Beck, ).…”
Section: Introductionmentioning
confidence: 99%